Human Resource Development Model in Small and Medium Enterprises Kemplang Crackers in Palembang City - Trihandayani, Zaleha; Yamaly, Fadhil; Dzaky Fawwaz, Ahmad (International Journal of Management Science and Information Technology, 2023)
Employees in small and medium enterprises of kemplang crackers in the city of Palembang are only directed to be able to work from skills that have been held informally and passed down from generation to generation so that the employees' working abilities are still simple or traditional. As a superior product, some kemplang crackers in Palembang are only able to survive in the local market and nationally, although a small part has penetrated the international market. Development style human resources in kemplang cracker small and medium businesses in Palembang City aims to improve the knowledge and skills of employees of small and medium kemplang cracker businesses in Palembang City so that employees work better and produce kemplang crackers of even better quality. Example: Taiwanese kemplang crackers are superior in the international market compared to Palembang kemplang crackers because they contain less water and the process of eating them is simpler. expected Kemplang crackers in Palembang City will not be left behind with the unique characteristics of employees' ability to process and manage kemplang crackers better in terms of knowledge, skills, and emotional intelligence. The research methodology used internally and externally is empirical-descriptive which is adequately obtained from research informants in the field (field research), and the research design used is conclusive, especially descriptive with a purposive sampling method. The findings from this research are a model of human resource development in small and medium businesses of kemplang crackers in Palembang City. The continuation of this research is research on developing a human resource development model in small and medium businesses kemplang crackers in Palembang City.